Revival of the Moral Traditions in Red Army During the Great Patriotic War - E. G. Guzhva (Vestnik MGIMO-Universiteta)
On the eve of the 70th anniversary of the Victory in the Great Patriotic War, it is important to analyze the moral factors that contributed to the uplift in the Red Army and the manifestation of mass heroism to defend the Fatherland. During the ordeal, when the fate of the country hung in the balance, the Soviet leadership was forced to revert to the heroic pages of national history and raise the patriotic spirit and the offensive of the armed forces on the front and high productivity at home. Since the 40s of the 19th century in the Russian army it was considered a holy tradition to start the evening roll call from the heroes. During the Great Patriotic War, the tradition was revived. Thus, according to the order of People's Commissar of Defense of the September 8,1943 the hero of the Soviet Union Alexander Matrosov was enlisted in the lists of the 1st company of 254-th Guards Rifle Regiment. Thus, the traditions of the Russian army, revived during the Great Patriotic War, testifies to their eternal spiritual values in matters of moral and patriotic education of servicemen of the Russian armed forces. This historical and pedagogical analysis is of great importance for the spiritual, moral and patriotic education of youth and soldiers of the Russian army at the present stage of development of society.